Reliability of pressure-volume loop parameters derived from transthoracic echocardiography in patients undergoing hemodialysis - Dinara Galiyeva; Zaukiya Khamitova; Aizhan Zhankorazova; Ayan Nurkesh; Dinara Jumadilova; Bauyrzhan Toktarbay; Murat Mukarov; Alexey Kokoskho; Abduzhappar Gaipov; Alessandro Salustri (PLoS ONE, 2026)
Background The pressure-volume (PV) relationship remains a key tool for assessing cardiac function. PV loop derived parameters, including end-systolic elastance (Ees), effective arterial elastance (Ea), ventriculo-arterial coupling (VAC), stroke work (SW), pressure-volume area (PVA), and work efficiency (WE), are valuable tools, but reproducibility data are scarce. Objective To evaluate the inter- and intra-observer variability of PV loop parameters derived from transthoracic echocardiography images in patients undergoing hemodialysis. Methods Twenty-five adult patients with end-stage renal disease undergoing maintenance hemodialysis were randomly selected. PV loops were reconstructed using Q-Strain software (version 1.3.0.79, Medis, Leiden, the Netherlands), and parameters including Ees, Ea, VAC, SW, PVA, and WE were calculated. Two experienced readers performed measurements for inter-observer analysis; one reader repeated measurements one week apart for intra-observer analysis. Reliability was assessed using intraclass correlation coefficients (ICC) and Bland-Altman plots. Results Inter-observer agreement was excellent for SW 0.96 (0.91–0.98) and PVA 0.95 (0.87–0.98), good for Ees 0.90 (0.77–0.96) and Ea 0.79 (0.49–0.91), and moderate for VAC 0.68 (0.23–0.85) and WE 0.72 (0.28–0.79). Intra-observer agreement was excellent for Ees 0.96 (0.90–0.98), Ea 0.98 (0.94–0.99), SW 0.98 (0.96–0.99) and PVA 0.98 (0.96–0.99), and good for VAC 0.78 (0.51–0.91) and WE 0.85 (0.65–0.94). Bland-Altman analysis showed minimal bias for Ees, SW and PVA, whereas Ea, VAC and WE exhibited proportional bias. Conclusions PV loop-derived parameters obtained via transthoracic echocardiography demonstrate good-to-excellent reproducibility, particularly for Ees, Ea, SW and PVA. VAC and WE show moderate variability, suggesting careful interpretation of these parameters in clinical and research settings.